2003
DOI: 10.1063/1.1542659
|View full text |Cite
|
Sign up to set email alerts
|

Study of the electrical activation of Si+-implanted InGaAs by means of Raman scattering

Abstract: Raman scattering has been used to study the lattice recovery and electrical activation of Si ϩ -implanted In 0.53 Ga 0.47 As achieved by rapid thermal annealing. The degree of crystallinity recovery of totally amorphized samples is studied for annealing temperatures between 300 and 875°C. A good degree of recovery is achieved for an annealing temperature of 600°C. Higher annealing temperatures are required to electrically activate the Si donors. The observed LO phonon-plasmon coupled modes allow us to monitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Which signals the onset of electrical activation of the implanted impurities [14]. As increasing of the annealing temperature and energy, the spectrums show four Raman peaks to reflect the increasing electrical activation of the implanted dopants mentioned from previous literature [14]. The similar four Raman peaks are observed in the spectrum of MWA 4P and RTA 700°C and 750°C.…”
Section: Spectral Analysissupporting
confidence: 65%
See 2 more Smart Citations
“…Which signals the onset of electrical activation of the implanted impurities [14]. As increasing of the annealing temperature and energy, the spectrums show four Raman peaks to reflect the increasing electrical activation of the implanted dopants mentioned from previous literature [14]. The similar four Raman peaks are observed in the spectrum of MWA 4P and RTA 700°C and 750°C.…”
Section: Spectral Analysissupporting
confidence: 65%
“…With a further increase of annealing temperature and energy, the only noticeable effect on the Raman spectrum of annealed samples at RTA 600°C and MWA 3P is an intensity reduction. Which signals the onset of electrical activation of the implanted impurities [14]. As increasing of the annealing temperature and energy, the spectrums show four Raman peaks to reflect the increasing electrical activation of the implanted dopants mentioned from previous literature [14].…”
Section: Spectral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…12 More recent work has shown that it is possible to study the doping concentration in InGaAs using calibrated Raman spectroscopy and the goal of this work is to similarly apply calibrated Raman spectroscopy to investigate the activation of implanted Si in InAs. [13][14][15] EXPERIMENTAL Commercially available, 500 lm thick, 3 in. Zn-doped InAs wafers with a background p-type concentration of 3 Â 10 17 cm À3 grown using the liquid encapsulated Czochralski process were implanted with 20 keV, Si þ over a range of doses from 1 Â 10 13 to -1 Â 10 15 cm À2 at a 7 tilt and 25 rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous authors have used Raman scattering to measure free carrier concentrations making use of the fact that LO phonons will readily couple with the plasma oscillations of free carriers in InAs and other polar, III-V materials. 13,14,[21][22][23][24][25][26][27] The L þ phonon-plasmon coupled mode is especially sensitive to changes in the carrier concentration at high n-type carrier concentrations in InAs where Raman shifts towards higher wavenumbers correspond to increasing free electron concentrations. Diffusion of Si in InAs beyond the initial implanted profile may increase the active sheet number measured by Hall effect precluding accurate carrier concentration estimates without corresponding Si diffusion data.…”
Section: Introductionmentioning
confidence: 99%